Hepatitis B Infection in Outpatients and Pregnant Women Visiting a Mission Hospital in Ghana - Margaret Addo; Sule Apaame; Michael Abbey Ghanney; Hannah Konadu Adu; Michael E. DeWitt; Seth Offei Addo (Public Health Challenges)
ABSTRACT Millions of individuals worldwide suffer from hepatitis B, a serious, potentially fatal liver infection brought on by the hepatitis B virus (HBV). Although vaccines are available for HBV, infections continue to persist in Ghana. This study reports the prevalence of HBV infections in outpatients and pregnant women attending antenatal care at the Seventh‐day Adventist (SDA) Hospital in Gbawe, Ghana. This retrospective cohort study involved the review of de‐identified medical records of outpatients and pregnant women who visited the hospital between 2022 and 2024. Data on their HBV infection status, sex and age were analysed using R version 4.4.1. A total of 531 outpatients and 768 pregnant women visited the hospital during the study period. The prevalence of HBV infection was 7.5% in outpatients and 3.9% in pregnant women. It was observed that outpatients were more likely to be hepatitis B surface antigen (HBsAg) positive (OR = 2.0, 95%CI = 1.24–3.28, p = 0.005). It was also seen that HBV prevalence increased from 2022 to 2023 and decreased in 2024. There is a need for more educational campaigns to raise awareness of HBV infections, especially in pregnant women due to the risk of mother‐to‐child transmission. Furthermore, vaccinations need to be made affordable and easily accessible to the general population to ensure maximum coverage within the country.